Tentmaking dan Peranannya dalam Memproklamirkan Nama Allah di Dalam Pelayanan Lintas Budaya - Darmanto Darmanto (SANCTUM DOMINE: JURNAL TEOLOGI, 2015)
Reaching the unbelievers or proclaiming the gospel is always to be a part of the believers life responding to the Great Comission. On the other hand, recently, preaching the gospel seems just stay in the same place. It is because some factors such as : the changing of cultures and approach method. Due to those changing, method and appoaches are needed that are relevant with today’s context. The God’s servants (Tentmaker) with “secular” profesion (Tentmaking) will be an alternate to make a new access in a new place. By this way, the gospel preaching process will go well.